Congenital generalized lymphangiectasia: a rare developmental disorder for non-immune fetal hydrops - Cristiane Rúbia Ferreira; Verônica Sibre; Regina Schultz; Ana Maria Andrello Gonçalves Pereira de Melo Melo; Silvia Maria Ibidi; Jackeline Della Torre (University of São Paulo, 2015)
Firstly described by Rudolf Virchow in the 19th century, congenital generalized lymphangiectasia is a rare entity characterized by dilation of lymphatic vessels, and was recently classified in primary or secondary lymphangiectasia. Generalized forms may be diagnosed during pre-natal follow-up with ultrasound examination, and, depending on its severity, the newborn outcome is very poor. The authors report the case of a female newborn with a previous diagnosis of fetal hydropsy who was born after a full-term gestation with respiratory failure due to bilateral voluminous pleural effusion and ascites. Physical examination also disclosed syndromic facies. Despite all efforts of the intensive supportive care, the patient died after 24 days of life. The autopsy findings were consistent with the diagnosis of congenital pulmonary lymphangiectasia. The authors call attention to this rare diagnosis in patients with cavitary effusion and respiratory insufficiency at birth